2022
DOI: 10.1097/gox.0000000000004313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life (BREAST-Q) and Scar Quality (POSAS) after Breast Augmentation

Abstract: Background: This study examines the effects of breast augmentation on women who underwent surgery in Germany regarding their quality of life (QOL) and scar quality using patient-reported surveys. The purpose of this study was to determine if there is an increase in women’s QOL after surgery compared with preoperative, and to evaluate their postoperative scar quality. Methods: A prospective monocentric study was conducted on 50 women who underwent breast augmentation with nanotextured silicone-filled implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, the MSS and POSAS were used to evaluate the cosmetic outcomes. The cosmetic outcomes of surgical scars and QOL are often related in adults [21][22][23]. Brown reported that the clinician's objective scar rating differed signi cantly from the patient-rated scar severity in adult patients (> 16 years) with heterogenous types of scars presenting at an outpatient department, and that the latter rating correlated with subjective psychological distress [24].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the MSS and POSAS were used to evaluate the cosmetic outcomes. The cosmetic outcomes of surgical scars and QOL are often related in adults [21][22][23]. Brown reported that the clinician's objective scar rating differed signi cantly from the patient-rated scar severity in adult patients (> 16 years) with heterogenous types of scars presenting at an outpatient department, and that the latter rating correlated with subjective psychological distress [24].…”
Section: Discussionmentioning
confidence: 99%
“…2 Luong et al found, like in other studies, that physical well-being suffered relative to baseline at the study endpoint of 6 months. [3][4][5][6] It was hypothesized that patients tolerate some discomfort in exchange for significant gains in appearance and psychosocial and sexual well-being.…”
mentioning
confidence: 99%
“…1 This study joins the literature including other published studies using the BREAST-Q to assess improvement in QoL with breast augmentation surgery. [2][3][4][5][6][7][8] This multicenter/multisurgeon study from the Netherlands is the largest of these studies performed to date, investigating 1405 patients treated from August of 2016 to September of 2021. Although all implants were silicone and textured, and placed through an inframammary fold incision, implants varied in volume and plane of placement, including subglandular, subfascial, and submuscular approaches.…”
mentioning
confidence: 99%